2009
DOI: 10.1108/02630800910985090
|View full text |Cite
|
Sign up to set email alerts
|

The built environment interdiscipline

Abstract: Purpose -The built environment subject area is now well-established as a recognised field of study. However, because of its vocational orientation it is usually defined in terms of a particular range of professional activities and aptitudes. In consequence the theoretical nature of its academic knowledge base is poorly developed. This has consequences for research and teaching practice within the field which are explored in this paper.Approach -Using established literature on the historical approaches to knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Nevertheless, it is argued here that presently, the CM discipline's methodological predilections and those of the researcher acting within it tend to dominate methodological judgements. disciplines embracing methodological paradigms that characterise that discipline's extent of (methodological) development (Chynoweth, 2009) and is perhaps what Oakley (1999) meant, when referring to paradigmatic choice being affected by 'fashions'.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Nevertheless, it is argued here that presently, the CM discipline's methodological predilections and those of the researcher acting within it tend to dominate methodological judgements. disciplines embracing methodological paradigms that characterise that discipline's extent of (methodological) development (Chynoweth, 2009) and is perhaps what Oakley (1999) meant, when referring to paradigmatic choice being affected by 'fashions'.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The BE sector is a sector within the construction industry that specifically encompasses a large number and range of participants involved in the design, construction, management, and maintenance of all forms of residential, non-residential, and civil engineering works, including their landscapes [17,18]. The BE discipline is becoming a well-established and recognised field of study by the international academic community [19]. As described by Griffiths [20] (p. 4), the BE discipline comprises of a "a range of practice-oriented subjects concerned with the design, development and management of buildings, spaces and places".…”
Section: Built Environment Disciplinementioning
confidence: 99%
“…The CIOB Education Framework, for example, must be followed when applying for CIOB accreditation/re-accreditation and to inform programme design or review in CM education (CIOB 2013). Chynoweth (2009) discussed the built environment as an applied, but theoretically coherent, interdiscipline. Further, according to Gajendran et al (2014), the construction manager's role in project-based organisations is dominated by complexity, uncertainty and interconnectivity.…”
Section: Nature Of Construction Higher Educationmentioning
confidence: 99%
“…One of the key issues associated with modular learning and assessment in UG construction programmes seems to be the lack of coherence; that is, assessing students' ability to connect specific subject content learned within different modules in order to solve complex problems. For example, Chynoweth (2009) found that law-related modules are rarely integrated with other subjects and law subjects were delivered and assessed exclusively within their module. It was noted that a wider interdisciplinary curriculum integrating all necessary subject domains (technology, management, law and so on) is required.…”
Section: Assessment In Undergraduate Construction Programmesmentioning
confidence: 99%